Solve your child's sleep problems eaudiobook - Ferber, Richard (Tantor Media, 2012)
Does your child: Have difficulty falling asleep? Wake in the middle of the night? Suffer sleep terrors, sleepwalking, or nighttime fears? Have difficulty waking for school or staying awake in class? Snore, wet the bed, or head bang? In the first major revision of his bestselling, groundbreaking classic, Dr. Richard Ferber, the nation's foremost authority on children's sleep problems, delivers safe, sound ideas for helping your child fall and stay asleep at night and perform well during the day. Incorporating new research, Dr. Ferber provides important basic information that all parents should know regarding the nature of sleep and the development of normal sleep and body rhythms throughout childhood. He discusses the causes of most sleep problems from birth to adolescence and recommends an array of proven solutions for each so that parents can choose the strategy that works best for them. Topics covered in detail include: Bedtime difficulties and nighttime wakings Effective strategies for naps Sleep schedule abnormalities A balanced look at co-sleeping New insights into the nature of sleep terrors and sleepwalking Problems in setting limits Sleep apnea, narcolepsy, bed-wetting, and head banging Solve Your Child's Sleep Problems offers priceless advice and concrete help for a whole new generation of anxious, frustrated, and overtired parents.